Hydrogels Generated from Cyclic Poly(2‐Oxazoline)s Display Unique Swelling and Mechanical Properties. Issue 7 (16th December 2020) - Trachsel, Lucca; Romio, Matteo; Zenobi‐Wong, Marcy; Benetti, Edmondo M.
Abstract: Cyclic macromolecules do not feature chain ends and are characterized by a higher effective intramolecular repulsion between polymer segments, leading to a higher excluded‐volume effect and greater hydration with respect to their linear counterparts. As a result of these unique properties, hydrogels composed of cross‐linked cyclic polymers feature enhanced mechanical strength while simultaneously incorporating more solvent with respect to networks formed from their linear analogues with identical molar mass and chemical composition. The translation of topology effects by cyclic polymers into the properties of polymer networks provides hydrogels that ideally do not include defects, such as dangling chain ends, and display unprecedented physicochemical characteristics. Abstract : Unique polymer topology effects by cyclic macromolecules coupled to a synthetic strategy that reduces the occurrence of structural irregularities lead to polymer networks that can incorporate more solvent while simultaneously being stiffer compared to compositionally similar hydrogels formed from linear analogues.